Vibrational anharmonicity of A-band related optical center and its temperature dependence studied by femtosecond laser excitation in bulk natural diamond - Kudryashov, Sergey; Danilov, Pavel; Smirnov, Nikita; Kovalov, Volodymyr (Communications in Physics, 2024)
Unusual A-band spectra with well-resolved quasi-periodical phonon progressions of multiple peaks (N\(\sim \)9) were excited in a natural diamond by 515-nm, 300-fs laser pulses at variable pre-heating temperatures of 24-200oC. The non-radiative multi-phonon part of the relaxation path was comparable with the total relaxation energy (zero-phonon line energy), pointing out some extended defects (e.g., dislocations) as the recombination center of the A-band emission. The derived temperature dependences of the peak intensities, separations and half-widths of the separate spectral peaks in the A-band phonon progressions indicate the different trends for vibration-free zero-phonon transition and vibration-related lower-energy transitions to high vibrational levels of the bottom state – lower thermal damping and more softened phonon for the zero-phonon transition, also implying the extended defect origin of the A-band photoluminescence.